Juliet’s run as seen on screen: reinterpretation of the past through camera lenses - Krisskaya, Lidia (Monitor ISH, 2021)
This article analyses Juliet’s famous run from the filmed ballet performance Romeo and Juliet’ 2 and looks at the camera as a subject in history. As the Angel of History3 , the movie camera is an open-eyed witness, looking into the past while having its back turned to the future. But the camera is more than a witness - it is simultaneously the executor of someone else’s will and the narrator of its own story.
Keywords: Balet; Romeo in Julija (balet); Video umetnost